LEGAL RISKS WHEN CONCLUDING PUBLIC PROCUREMENT CONTRACTS - Ilyassova, Самал Мырзамуратқызы; Aldabergenova , Нонна Алдабергенқызы; Zhussupbekova, Мадина Қойшыбайқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
In this article, the authors theoretically and practically examine the issues of legal risks when concluding public procurement contracts, identify the main ones, explain the patterns of their occurrence and suggest ways to minimize them. The purpose of the article is to identify the main legal risks when concluding public procurement contracts. The main objective of the article is to propose ways to reduce legal risks by analyzing practice and current legislation. Brief description of the scientific and practical significance of the work. The growing interest of scientists in the object of research raises many questions that require research to solve complex problems. At the same time, for legal doctrine it is important to study the legal risks when concluding public procurement contracts from a theoretical point of view. Research in a scientific article can help prevent malpractice in practice. Brief description of the research methodology. This research work requires a comprehensive analysis, therefore, during the study, empirical and theoretical methods of general and special scientific research are systematically used. Main results and analysis, conclusions of the research work. As a result of the study, the main legal risks were identified and systematized, and experience was analyzed. The article shows the conclusions on the improvement of legislation in the field of public procurement, which also contributes to the improvement of legal culture. The value of the research is that the results of the study can be used in lectures on branches of civil law and as scientific material for academic researchers. Practical significance of the results of the work. Representatives of customers carrying out public procurement and representatives of control authorities can use the results of the work in their daily activities.